Bengal politics : documents of the Raj, Vol. II (1940-43) - Rahim, Enayetur; Rahim, Joyce L. (Dhaka, Bangladesh : University Press Limited, 1999)
Chiefly comprises fortnightly reports of the Governor of Bengal to the Viceroy and Governor-General of India and their replies, 1936 to 1947.
v. 1. 1936-39 -- v. 2. 1940-43 -- v. 3. 1944-1947.
"Bangladesh: towards the year 2000 publications programme sponsored jointly by UPL and the Ford Foundation"--Half t.p.
Includes index.
BIED, GenEd
Keywords: Bengal (India) -- Politics and government -- Sources